1975
DOI: 10.1159/000197701
|View full text |Cite
|
Sign up to set email alerts
|

The Histological Classification of Duodenitis in Fibreoptic Biopsy Specimens

Abstract: Recent advances in biopsy techniques using fibreoptic instruments have refocussed attention on the condition of non-specific duodenitis. Investigation of the topography of duodenitis and its relationship to possible aetiological factors and to duodenal ulcer calls for a proper histological classification. Such a classification is proposed based on the subjective appearances and a quantitative examination of 747 fibreoptic biopsy specimens in a wide range of clinical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

1978
1978
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(32 citation statements)
references
References 7 publications
2
29
1
Order By: Relevance
“…If the number of chronic inflammatory cells in the mucosal lamina propria is used as a criterion of chronic duo denitis, we must conclude on the basis of our cell counts that no relationship exists with alcohol ingestion. On the other hand, certain other stigmata of chronic duodenitis were found exclusively or primarily among chronic alcoholics, namely goblet cell hyperplasia, gas tric metaplasia (5,6,11,26), and villus and epithelial changes (6, 8. 17, 24, 26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the number of chronic inflammatory cells in the mucosal lamina propria is used as a criterion of chronic duo denitis, we must conclude on the basis of our cell counts that no relationship exists with alcohol ingestion. On the other hand, certain other stigmata of chronic duodenitis were found exclusively or primarily among chronic alcoholics, namely goblet cell hyperplasia, gas tric metaplasia (5,6,11,26), and villus and epithelial changes (6, 8. 17, 24, 26).…”
Section: Discussionmentioning
confidence: 99%
“…without knowledge of the patients' history or clinical findings. As a means of quantitating the chronic inflammatory infiltrate, lymphocytes and plas ma cells in all biopsies were counted using the follow ing, well-established technique (16,21,26). A 5.0-mm square disc (Thomas.…”
Section: Methodsmentioning
confidence: 99%
“…The activity reflected by invasion of polymorphs into and degenerative changes of the epithelial elements was recorded as well as the presence of intestinal metapla sia (IM). Also, duodenitis was graded according to the Whitehead classification [20]: 0 = normal mucosa: I = mild duodenitis with excessive cellularity of the lam ina propria but well-kept villous architecture; 2 = moderate duodenitis with increased cellularity of the lamina propria and abnormalities of the superficial epithelium, and 3 = severe duodenitis with erosion, loss of the villous processes and heavy inflammatory cell infiltration. Neutrophil polymorph infiltration was seen as a sign of activity and gastric epithelial metaplasia (GM) was looked for.…”
Section: Methodsmentioning
confidence: 99%
“…The most used histological classification of duodenitis was proposed by Whitehead et al [12] but others have been reported [5]. In grade I (mild) duodenitis the only significant alteration is an increase in the cellularity of the lamina propria.…”
Section: Endoscopic and Histological Features In Duodenitis And Theirmentioning
confidence: 99%
“…The grade of activity of duodenitis is thought to be indicated by the number of neutrophils in the inflammatory infiltrate [12]. It has been suggested, however, that the presence of neutrophil leukocytes may indi cate a superimposed acute process not per taining to chronic duodenitis [13].…”
Section: Endoscopic and Histological Features In Duodenitis And Theirmentioning
confidence: 99%